2020
DOI: 10.5334/gjgl.907
|View full text |Cite
|
Sign up to set email alerts
|

The Anaphor Agreement Effect is not about featural deficiency: Evidence from Avar

Abstract: This paper discusses two analyses of the Anaphor Agreement Effect (AAE, Rizzi 1990) in the light of novel data from Avar. By demonstrating that Avar anaphors trigger full, non-trivial agreement on the φ-probe, I argue that the Avar data instantiate a genuine exception to the AAE. I then compare two competing analyses of binding and the AAE: an account whereby anaphoric dependencies arise via the syntactic operation Agree (Murugesan 2019), and a theory deriving the inability of the anaphors' φ-features to trig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Subsequent cross-linguistic work has shown that languages make use of a wide range of strategies, all conspiring to avoid covarying φ -agreement with anaphors (e.g. Woolford 1999;Haegeman 2004;Tucker 2011;Patel-Grosz 2014;Sundaresan 2014Sundaresan , 2016Murugesan 2019;Preminger 2019;Rudnev 2020). In this short paper, I identify and confirm a prediction arising from two particular observations by Woolford (1999), thus also expanding our understanding of possible AAE strategies cross-linguistically.…”
mentioning
confidence: 54%
“…Subsequent cross-linguistic work has shown that languages make use of a wide range of strategies, all conspiring to avoid covarying φ -agreement with anaphors (e.g. Woolford 1999;Haegeman 2004;Tucker 2011;Patel-Grosz 2014;Sundaresan 2014Sundaresan , 2016Murugesan 2019;Preminger 2019;Rudnev 2020). In this short paper, I identify and confirm a prediction arising from two particular observations by Woolford (1999), thus also expanding our understanding of possible AAE strategies cross-linguistically.…”
mentioning
confidence: 54%
“…Rudnev 2020 criticizes the present analysis on the basis of biabsolutive constructions in Nakh-Daghestanian languages. These in fact exhibit two different sets of agreement values on the verb and the auxiliary, as illustrated by the Archi example in (i), and this seems to go against the stated conclusion about Archi, that T is the only probe.…”
mentioning
confidence: 84%
“…Taken together, we draw on these assumptions for the analysis of ki-marking. In (67), we clearly see that ki-marking involves a change in word order, which can be viewed as movement of the indirect object to a higher position (though see (79) for discussion of an alternative). 18…”
Section: B ámentioning
confidence: 99%
“…By assumption, Appl only selects for a PP headed by ki in a rightward specifier. On this alternative analysis, subject binding would look as in (79). ( 79…”
Section: Binding From the Indirect Objectmentioning
confidence: 99%